Application of Problem Based Learning Model in Learning to Writing Response Texts in Grade IX of Smp Negeri 6 Semarang - Nugroho, Wahyu Adi; Siti Ulfiyani; Theresia Danik Kristanti; Ngatmini (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
The purpose of this study was to determine the application of the problem based learning model in learning to write response texts for class IX of SMP Negeri 6 Semarang. The method used is qualitative description, using data sources in the form of interviews, observations, and documentation. Qualitative research was chosen because it was able to carry out an intensive approach between resource persons and researchers in the field directly. The results of this study are that the factors of the Problem Based Learning (PBL) model in response texts are contextual learning, implementation of the Merdeka curriculum, implementation of the Cultural Responsibility Teacher (CRT). The steps in learning response texts in the Problem Based Learning (PBL) model are making Student Worksheets (LKPD), implementing work groups, presenting group work results. Meanwhile, the benefits of learning response texts with the Problem Based Learning (PBL) model are that students in class IX of SMP Negeri 6 Semarang are able to think critically and students in class IX of SMP Negeri 6 Semarang are able to apply creativity values ​​in working on response texts based on the Problem Based Learning (PBL) model.